49.5k views
4 votes
Solve the system by substitution -4x-3y=-21x=y

User Tibin Paul
by
5.4k points

1 Answer

4 votes

We have the system of equations:


\begin{gathered} -4x-3y=-21 \\ x=y \end{gathered}

We have to solve it by substitution.

The second equation gives the information to substitute, for example, x with y. We perfomr the substitution in the first equation:


\begin{gathered} -4y-3y=-21 \\ -7y=-21 \\ y=(21)/(7) \\ y=3 \end{gathered}

Then, with the value of y and the second equation we have:


x=y=3

Answer: the solution to the system is x=3 and y=3.

User Alextsc
by
6.2k points